Examining the motivation and the implementation of early mobilization in post-lower extremity operations - Restutin, Siti; Handian, Feriana Ira; Firdaus, Achmad Dafir (Palembang MediRose Publisher, 2023)
Background: Early mobilization is an effective approach for the healing process following lower extremity surgery. However, its successful implementation requires self-encouragement and motivation from patients. Objective: This study aimed to investigate the relationship between motivation and the implementation of early mobilization in patients undergoing lower extremity surgery. Methods: A cross-sectional analytic descriptive study was conducted involving 41 respondents who were selected using a purposive sampling technique. Data were collected through motivation questionnaires and early mobilization observation sheets. The collected data were analyzed using the Spearman Rho test with a significance level of ? = 0.05. Results: Out of the 41 respondents, 21 (51.2%) showed moderate levels of motivation for early mobilization, while 20 (48.8%) demonstrated sufficient to good implementation of early mobilization. The statistical test revealed a significant relationship between motivation and early mobilization (p=0.035 or p<0.05), with an r-value of 0.329. Conclusions: The results highlight a significant correlation between motivation and early mobilization, which is closely associated with psychological mechanisms. The need for quick recovery serves as an encouragement for optimal early mobilization. Higher motivation levels contribute to better implementation of early mobilization. Considering the importance of motivational variables, it is suggested that nurses increase educational exposure and involve the patient’s family in order to enhance motivation for early mobilization.